2009
DOI: 10.1540/jsmr.45.15
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology underlying irritable bowel syndrome -From the viewpoint of dysfunction of autonomic nervous system activity-

Abstract: Although irritable bowel syndrome (IBS) is the most common gastrointestinal disease and is found in up to 50% of patients referred to gastroenterologists, its pathogenesis remains unexplained. Lately most attention has been focused on visceral hypersensitivity related to dysfunction of the autonomic nervous system. Although there have been many reports regarding the autonomic nervous system in IBS patients, the results have not always been consistent. In many studies, increased sympathetic nervous system activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 22 publications
4
48
3
3
Order By: Relevance
“…Although autonomic pathways are considered key in maintaining normal brain-gut interactions (Manabe et al 2009), our results suggest that, in response to acute psychosocial stress, the sympathetic branch of the autonomic nervous system is functioning normally in IBS. Furthermore, when comparing the methodological approach between studies, it seems that the SNS response in IBS is dependent on the type of stressor used.…”
Section: Discussionmentioning
confidence: 64%
“…Although autonomic pathways are considered key in maintaining normal brain-gut interactions (Manabe et al 2009), our results suggest that, in response to acute psychosocial stress, the sympathetic branch of the autonomic nervous system is functioning normally in IBS. Furthermore, when comparing the methodological approach between studies, it seems that the SNS response in IBS is dependent on the type of stressor used.…”
Section: Discussionmentioning
confidence: 64%
“…Noradrenaline is a neurotransmitter of the autonomic nervous system which is known to be altered in IBS (Manabe et al 2009). …”
Section: The Impact Of Maternal Separation On the Brain-gut Axismentioning
confidence: 99%
“…Despite the fact that the pathophysiology of IBS is poorly understood, it has been recently reported that the main pathophysiological mechanisms involve altered visceral sensitivity, abnormal gut motility and dysfunction of autonomic nervous system [3,4]. Serotonin, secreted by enterochromaffin cells and mast cells at the level of gut mucosa, is believed to modify the visceral sensitivity and regulate the gut motility and secretion [4,5].…”
Section: Introductionmentioning
confidence: 99%